PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP KESULITAN BELAJAR KIMIA KELAS XI SMA N 11 SEMARANG - Amelia Fahmi; Andari Puji Astuti (Universitas Muhammadiyah Semarang, 2017)
Characteristics of chemistry subject matter which most of the concept is abstract, causing problems arise that is student learning difficulties. It is influenced by several factors, one of which is the external factor derived from the teacher. This study aims to determine the influence of pedagogical competence of teachers to students' learning difficulties on chemistry subjects. The research was conducted in SMA Negeri 11 Semarang with the subject of the research is the students of class XII MIPA. The research method used is descriptive qualitative, with data retrieval technique through questionnaire and interview. The results showed that teacher pedagogic competence has an effect on student's learning difficulties. Keywords: pedagogic competence, learning difficulties, chemistry.